Executive Function Late Effects in Survivors of Pediatric Brain Tumors and Acute Lymphoblastic Leukemia - Winter, Amanda L. (J Clin Exp Neuropsychol, 2014)
BACKGROUND: Survivors of pediatric brain tumors (BT) and acute lymphoblastic leukemia (ALL) are at risk for neurocognitive late effects related to executive function. PROCEDURE: Survivors of BT (48) and ALL (50) completed neurocognitive assessment. Executive function was compared to estimated IQ and population norms by diagnostic group. RESULTS: Both BT and ALL demonstrated relative executive function weaknesses. As a group, BT survivors demonstrated weaker executive functioning than expected for age. Those BT survivors with deficits exhibited a profile suggestive of global executive dysfunction, while affected ALL survivors tended to demonstrate specific rapid naming deficits. CONCLUSION: Findings suggest that pediatric BT and ALL survivors may exhibit different profiles of executive function late effects, which may necessitate distinct intervention plans.